Diversidade e composição de aves em áreas remanescentes de floresta ombrófila mista e em plantações de Araucaria angustifolia e de Pinus sp. no sul do Brasil - Rossi, Liana Chesini (Universidade do Vale do Rio dos Sinos, 2015)
Araucaria forests are part of the Atlantic forest’s biome and are distributed over the southern regions of Brazil. Originally occupied an area of 25,379,316 hectares, which today remain least 12.6% of its original formation distributed in small and isolated fragments, where most no more than 50 ha. Initially, the loss of vegetal covering occurred due to extraction and wood logging and later due to agriculture, livestock and forestry. Selective logging and forestry were specially explored in the south of Brazil resulting in the substitution, fragmentation and isolation of natural areas, resulting in a reduction and loss of diversity of birds. Thus, this work aims to characterize the forest interior bird community of Araucaria forest with selective logging and areas of forestry activity with exotic species (Pinus sp.) and native species (Araucaria angustifolia). The aim of the first chapter was to test whether selective logging can cause changes in the richness and species composition in the bird community. Using the methodology of point-counts with fixed radius, they were sampled richness and abundance of species. To this, avifauna surveys were conducted within three protected areas characterized by Mixed Rain Forest: Três Barras National Forest (selective logging more than 40 years) Irati National Forest (primary forest, without selective logging) and Pizzatto Forest Reserve (recent selective logging). Using an exploratory technique called ‘‘Rank Occupancy–Abundance Profiles (ROAPs),’’ it was determined the sensitivity of each species. As species richness, did not differ significantly between protected areas (F1,33 = 1.805, p = 0.180), but the species composition was different (F = 5, 286, p <0.0001). About the degree of sensitivity, FI presented a higher number of species classified as sensitive 65% (n = 61), followed by RFP in 60% (n = 58) and FTB, 53% (n = 45) sensitive species. Through cluster analysis, which considered the sensitivity and the habitat of the species, demonstrated a greater similarity between the FI and the RFP when compared to FTB, which presented different composition compared the two other areas. Thus, different selective logging intensities resulted in compositions of different species between protected areas. This may have occurred because of forest degradation caused by selective logging by modifying natural habitats, continuing in open areas and increasing the size of the edges, allowing the occupation of species able to survive in this environment, thus increasing species richness. The areas studied, even with selective logging are able to maintain a high number of sensitive species, and endangered species, therefore, are important areas for conservation should be preserved. To answer the second objective, the same methodology was applied at the interior of three vegetal formations: Atlantic forest with selective logging, plantation of a native species Araucaria angustifolia and plantation of an exotic species Pinus sp., all of them located at the Três Barras National Forest. No significant differences were recorded in wealth among the three forest types (F2,33 = 3,05, p = 0,6), however, the composition of species was different (F = 4,814, p <0,0001). Insectivores and forest dependent species were more frequent in the native forest with selective logging, and granivores and generalist species showed a closer relationship with the planting of exotic species. The difference of species composition between areas is explained by higher habitat heterogeneity in native forests, which increase resource availability, while plantation areas tend to be more homogeneous and resource-poor. The similarity of species richness between native forest and plantations may occur due to damages caused by selective logging at native forests, which results in a small number of recorded species. Furthermore, management techniques and the advanced age of plantations develop different strata in plantations increasing resource availability and therefore bird richness. Thus, it is concluded that plantations, mainly of native tree species, are able to include an birds associated with native forests, however, natural forest areas are irreplaceable because they contain a bird life with more specialists habits should be preserved.
Keywords: Comunidade de aves; Mata Atlântica; Espécies ameaçadas; Espécies sensíveis; Plantação de exótica; Plantação de nativa; Rank Occupancy Abudance Profiles (ROAP); Silvicultura; Birds community; Atlantic forest; Endangered species; Susceptible species; Exotic plantation; Forestry; ACCNPQ::Ciências Biológicas::Biologia Geral